Dibromidodi-mu-hydroxido-di-mu(3)-oxido-octaphenyltetratin(IV) - Yap, Q.L.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the centrosymmetric title compound, [Sn4Br2(C6H5)(8)O-2(OH)(2)], the four tin(IV) atoms are bridged by the hydroxo and oxo ligands, forming a ladder-like array of three edgeconnected Sn2O2 squares. The two independent tin atoms show distorted trigonal-bipyramidal SnC2O3 and SnC2O2Br coordination geometries.